2016
DOI: 10.1016/j.ecolind.2016.03.024
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Kuznets Curve hypothesis and the role of globalization in selected African countries

Abstract: Abstract:The present study incorporates globalization and energy intensity into the CO 2 emissions function and investigates the presence of Environmental Kuznets Curve (EKC) in 19 African countries for the time period of 1971-2012. We have applied the ARDL bounds testing approach to cointegration to examine the long run relationship in the variables. Our results confirmed the presence of cointegration between the series in Africa, Algeria, Angola, Cameroon, Congo Republic, Ghana, Kenya, Libya, Morocco, Nigeri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
93
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 227 publications
(133 citation statements)
references
References 69 publications
20
93
0
2
Order By: Relevance
“…The results support the EKC hypothesis for India, China, Korea, and Turkey. Shahbaz and Solarin [43] examined the existence of the EKC hypothesis for 19 African countries for the period of1971-2012 by using an ARDL bounds testing approach. The findings suggested that only six countries support the EKC hypothesis, and that globalization plays an important role from county to country in decreasing CO 2 emissions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The results support the EKC hypothesis for India, China, Korea, and Turkey. Shahbaz and Solarin [43] examined the existence of the EKC hypothesis for 19 African countries for the period of1971-2012 by using an ARDL bounds testing approach. The findings suggested that only six countries support the EKC hypothesis, and that globalization plays an important role from county to country in decreasing CO 2 emissions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Similar studies investigating the EKC hypothesis at the national level have been conducted by Kunnas and Myllyntaus () for Finland; Ozturk and Acaravci () for Turkey; Park and Lee () for the Republic of Korea; Brajer, Mead, and Xiao (), Jayanthakumaran and Liu (), and Liu, Zhou, and Wu () for China; Bekhet and Othman (), Saboori, Sulaiman, and Mohd (), and Saboori and Sulaiman () for Malaysia; Tiwari, Shahbaz, and Hye () for India; Katircioğlu () for Singapore; Shahbaz, Khraief, Uddin, and Ozturk () for Tunisia; Sugiawan and Managi () for Indonesia; Atasoy () for the United States; and Olale, Ochuodho, Lantz, and El Armali () for Canada. Furthermore, at the regional level, the EKC hypothesis has been tested by a number of scholars, such as Atici () for the central and eastern Europe; Pao and Tsai () for a panel of Brazil, Russia, India, and China countries; Acaravci and Ozturk () for Europe; Arouri, Youssef, M'henni, and Rault () for Middle East and North African countries; Ozcan () for Middle East countries; Bölük and Mert () for a panel of European Union countries; Ozturk () for Brazil, Russia, India, China, and South Africa countries; Heidari, Katircioğlu, and Saeidpour () for five Association of South East Asian Nations countries; Bilgili, Koçak, and Bulut () for 17 Organization for Economic Cooperation and Development countries; Shahbaz, Solarin, and Ozturk () for 19 African countries; Charfeddine and Mrabet () for 15 Middle East and North African countries; and Dong, Sun, Jiang, and Zeng () for 14 Asia‐Pacific countries. In addition, the EKC hypothesis has been examined at the global level by, for example, Alvarado, Ponce, Criollo, Córdova, and Khan (); Paramati, Alam, and Apergis (); Rasli, Qureshi, Isah‐Chikaji, Zaman, and Ahmad (); Shahbaz, Ozturk, Afza, and Ali (); Shuai et al (); Shuai et al (); and Ulucak and Bilgili ().…”
Section: Literature Reviewmentioning
confidence: 99%
“…To ensure the positive impact of agricultural coal energy and electricity energy on agricultural CO 2 emissions, there needs to be a policy of searching for and using renewable energy (wind, solar, biodiesel fuel) within the South African agricultural sector. There is large potential for bioenergy and hydroelectricity use in the South African agricultural sector, but it will require buy-in and investment [58]. Policy makers could also increase taxes on fossil fuel use within the agricultural sector, whilst subsidising renewable energies.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%